Childhood and adolescent influenza vaccination in Europe: A review of current policies and recommendations for the future. (3rd May 2016) - McGuire, Alistair; Drummond, Mike; Keeping, Sam
ABSTRACT: Children and adolescents experience some of the highest rates of influenza infection and the subsequent burden on both infected children and their parents/carers is substantial. Vaccinating children and adolescents against seasonal influenza has the potential to reduce the burden of disease in both vaccinated and unvaccinated individuals due to the pivotal role that younger age groups play in the transmission of infection. While countries such as the USA, Canada and the UK have consequently recommended the universal vaccination of children, the vast majority of European countries have not yet extended their vaccination policies to this age group. This review examines the rationale for childhood and adolescent vaccination against seasonal influenza and reviews current vaccination policies in Europe. We discuss key policy considerations for European countries that must be considered when extending vaccination programmes to younger age groups alongside recommendations for European policy makers based on our findings.